Diversity of bird-feeding guilds in Bukit Mas Village, North Sumatra, Indonesia - FAIRUZ HUSNA; NURHAYATI NURHAYATI; MUFTI PETALA PATRIA; NURUL LAKSMI WINARNI (Society for Indonesian Biodiversity, 2024)
Abstract. Husna F, Nurhayati, Patria MP, Winarni NL. 2024. Diversity of bird-feeding guilds in Bukit Mas Village, North Sumatra, Indonesia. Biodiversitas 25: 4572-4580. Birds are one of the essential components of the ecosystem. Like other organisms, birds provide significant services to maintain the balance of the ecosystem. Resource availability in different habitats may lead to differences in the composition of bird functional groups, such as feeding guilds. We conducted research to analyze differences between bird-feeding guilds of three habitats: residential areas, plantations, and forest edges. The research was conducted in Bukit Mas Village, Besitang District, North Sumatra, Indonesia. The village is one of the areas directly adjoining Gunung Leuser National Park. The observation was carried out from August to September 2023. Observation was conducted using the point-count method with a 100 m radius for 10 minutes. Sixteen observation points (150-200 m distance per point) were placed in residential areas and plantations, and eight observation points were placed in forest-edge. A total of 87 species and 1,703 individual birds were sighted within the observation, with the highest number found in residential habitats. The highest Shannon Diversity Index (SHDI) is found in forest edge habitat (H’=3.25), followed by plantation (H’=3.17) and residential habitat (H’=2.86). Extrapolation using the iNEXT package shows higher diversity in forest edge as well. The most abundant feeding guild found in the residential habitat were omnivores, while the commonest feeding guild in the plantation habitat were insectivores. In the forest edge habitat, the most abundant feeding guild was insectivore-frugivores. The forest edge habitat also has different least common feeding guilds, having three least feeding guilds, including piscivores, granivores, and insectivore-piscivores. NMDS analysis shows a closer similarity between residential areas and plantations based on species richness and a closer similarity between plantation and forest edge based on feeding guilds. Our result shows a negative correlation between canopy coverage and several feeding guilds. However, the correlation between understory coverage and some feeding guilds shows positive results. It might occur due to the foraging behavior of some birds from particular guilds. The variety of resources and feeding guilds found in different habitats suggested the importance of these habitats and the need to manage them as a landscape for protecting bird diversity.